Polygenic background modifies penetrance of monogenic variants for tier 1 genomic conditions - Akl C. Fahed (Nature Portfolio, 2020)
Genetic variation predisposes to disease via monogenic and polygenic risk variants. Here, the authors assess the interplay between these types of variation on disease penetrance in 80,928 individuals. In carriers of monogenic variants, they show that disease risk is a gradient influenced by polygenic background.